Ricochet : a novel [large type] - Moore, Taylor (Moore, Taylor. Garrett Kohl novel., 2025)
After an elite CIA counterespionage mission, Garrett Kohl returns home to Texas in hopes of settling down and carving out a normal life. But while learning the ropes of fatherhood and falling deeper in love with his high school crush, he is approached in secret by an engineer working at a nearby nuclear weapons plant who is in desperate need of his help. Utilizing a unique sill set, Garrett embarks on an off-the-books investigation and learns that Iranian operatives are potentially planning a devastating act of sabotage and destruction. Garrett musters the only help he can find -- a ragtag crew of outcasts and outlaws, some of whom he'd once put behind bars. Although they're from different walks of life, and opposite sides of the law, they hold in common the deep desire to protect their homes, their families, and their way of life on the remote, wild, and alluring Texas High Plains.